Who suffers the penalty? A panel data analysis of earnings gaps in Vietnam - Huu Chi Nguyen; Christophe Nordman; François Roubaud (Institute for the Study of Labor (IZA), 2013)
In spite of its predominant economic weight in developing countries, little is known about the informal sector earnings structure compared to that of the formal sector. Taking advantage of the VHLSS dataset in Vietnam, in particular its three wave panel data (2002, 2004, 2006), we assess the magnitude of various formal-informal earnings gaps while addressing heterogeneity at three different levels: the worker, the job (wage employment vs. self-employment) and the earnings distribution. We estimate fixed effects and quantile regressions to control for unobserved individual characteristics. Our results suggest that the informal sector earnings gap highly depends on the workers' job status and on their relative position in the earnings distribution. Penalties may in some cases turn into premiums. By comparing our results with studies in other developing countries, we draw conclusions highlighting the Vietnam's labour market specificity.
Keywords: J21; J23; J24; J31; O17; 330; informal employment; earnings gap; transition matrix; panel data; Vietnam